Cerebrovascular reactivity and white matter integrity. (29th November 2016) - Sam, Kevin; Peltenburg, Boris; Conklin, John; Sobczyk, Olivia; Poublanc, Julien; Crawley, Adrian P.; Mandell, Daniel M.; Venkatraghavan, Lakshmikumar; Duffin, James; Fisher, Joseph A.; Black, Sandra E.; Mikulis, David J.
Abstract : Objective: To compare the diffusion and perfusion MRI metrics of normal-appearing white matter (NAWM) with and without impaired cerebrovascular reactivity (CVR). Methods: Seventy-five participants with moderate to severe leukoaraiosis underwent blood oxygen level–dependent CVR mapping using a 3T MRI system with precise carbon dioxide stimulus manipulation. Several MRI metrics were statistically compared between areas of NAWM with positive and negative CVR using one-way analysis of variance with Bonferroni correction for multiple comparisons. Results: Areas of NAWM with negative CVR showed a significant reduction in fractional anisotropy by a mean (SD) of 3.7% (2.4), cerebral blood flow by 22.1% (8.2), regional cerebral blood volume by 22.2% (7.0), and a significant increase in mean diffusivity by 3.9% (3.1) and time to maximum by 10.9% (13.2) ( p < 0.01), compared to areas with positive CVR. Conclusions: Impaired CVR is associated with subtle changes in the tissue integrity of NAWM, as evaluated using several quantitative diffusion and perfusion MRI metrics. These findings suggest that impaired CVR may contribute to the progression of white matter disease.